Assessment of the Relationship Between Thinness Expectations, Body Satisfaction and Eating Attitude and Behavior - Nural Erzurum Alim (Universitas Airlangga, 2021)
Background: Body dissatisfaction is more common in adolescents and its prevalence is increasing in developed and developing countries. These situation is associated with unhealthy dieting behaviors. Purpose: This study aimed to evaluate the relationship between thinness expectations, body satisfaction, and eating attitudes and behaviors in interpersonal interaction.